2021
DOI: 10.1097/ta.0000000000003230
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support is strongly associated with recovery after injury

Abstract: BACKGROUND:The strength of one's social support network is a potentially modifiable factor that may have a significant impact on recovery after injury. We sought to assess the association between one's perceived social support (PSS) and physical and mental health outcomes 6 months to 12 months postinjury. METHODS:Moderate to severely injured patients admitted to one of three Level I trauma centers were asked to complete a phone-based survey assessing physical and mental health outcomes in addition to return to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…This suggests that systematic deprivation through the poverty cycle may have a significant impact on recovery trajectory and outcomes after injury. Strong support networks have been shown to be an important source of resilience and to positively impact recovery 33 . Herein, we found that within a census tract, certain factors that may be considered a proxy for weak social support networks, such as single parent households and noninstitutionalized people with disabilities, were associated with worse physical and mental health outcomes.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This suggests that systematic deprivation through the poverty cycle may have a significant impact on recovery trajectory and outcomes after injury. Strong support networks have been shown to be an important source of resilience and to positively impact recovery 33 . Herein, we found that within a census tract, certain factors that may be considered a proxy for weak social support networks, such as single parent households and noninstitutionalized people with disabilities, were associated with worse physical and mental health outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…Strong support networks have been shown to be an important source of resilience and to positively impact recovery. 33 Herein, we found that within a census tract, certain factors that may be considered a proxy for weak social support networks, such as single parent households and noninstitutionalized people with disabilities, were associated with worse physical and mental health outcomes. Finally, we found a greater level of education within the community to be protective against poor recovery, an association that has been previously described on an individual patient level.…”
Section: Discussionmentioning
confidence: 84%
“…Inadequate social support can especially impact patients recovering from traumatic injury, and social support has been shown to be a core component of many patients’ recovery in prior FORTE studies. 6 Another potential mechanism is through the stresses induced by the pandemic. During the pandemic, people have experienced stress about a wide range of topics, including fears of contracting the virus, mistrust of the medical system, and uncertainty about the future.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Poor perceived social support, social isolation, and loneliness are associated with higher morbidity and mortality and adverse functional outcomes after trauma. 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Our patients need more than just their physical wounds attended to if they are going to make "full" recovery. 36,37 We really need to follow the vision of President-elect David Livingston who has established their Center of Trauma Survivorship:…”
Section: Be Worthy Of Your Patientmentioning
confidence: 99%